OVERVIEW OF THE TECTONIC EVOLUTION OF THE SOUTHERN CENTRAL ANDES OF MENDOZA AND NEUQUÉN (35°-39°S LATITUDE) - Ramos V.A.; Kay S.M. (My University, 2006)
The southern Central Andes of Argentina between 35° and 39°S latitude can be divided into two sectors with contrasting geological histories. The boundary between the sectors coincides with the Cortaderas lineament. North of the Cortaderas lineament, the Andes record a foreland expansion of arc magmatism that is associated with contractional deformation in the Malargüe fold-and-thrust belt, and subsidence of the Río Grande foreland basin between 15 and 5 Ma. The peak expansion of deformation into the foreland occurred as late Miocene magmatic arc rocks erupted more than 500 km east of the trench and the San Rafael basement block was uplifted in central Mendoza. This stage was followed by the collapse of the basement uplift by normal faulting, the retreat of the magmatic arc, and the eruption of widespread late Pliocene to early Pleistocene within-plate lava flows in the Payenia region. Extensive Quaternary calderas and rhyolitic domes along the axis of the main Andes reflect crustal melting associated with basaltic underplating. In contrast, the structural evolution of the sector south of the Cortaderas lineament is dominated by the Late Cretaceous development of the Agrio fold-and-thrust belt, which underwent minor reactivations in the Eocene and the late Miocene. The post-Miocene Guañacos fold-and-thrust belt that has since developed along the axis of the main Andes concentrates neotectonic contraction. Arc magmatism in this sector is largely restricted to the axial area of the Andes. Both the sectors north and south of the Cortaderas lineament show evidence of an important episode of extension during the Oligocene to early Miocene, and for renewed extension in the Pliocene and the Pleistocene. The contrasting geological histories north and south of the Cortaderas lineament reflect differences in the geometry of the subducting plate, variations in crustal rheologies inherited from a more restricted distribution of Mesozoic rifts in the northern than the southern segment, and variations in the trench roll-back velocity through time. © 2006 Geological Society of America.
Keywords: AGRIO; ANDES; EXTENSION; FLAT-SUBDUCTION; MALARGüE; NEUQUÉN; PAYENIA; Cretaceous; Pleistocene; Pliocene; Miocene; Oligocene; Eocene; Mesozoic::Cretaceous; Мезозой::Меловая; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен